Axial length and optic disc size in normal eyes. Issue 1 (20th September 2006) - Oliveira, C; Harizman, N; Girkin, C A; Xie, A; Tello, C; Liebmann, J M; Ritch, R
Abstract : Aim: To investigate the relationship between optic disc area and axial length in normal eyes of white and black people. Methods: Consecutive eligible normal subjects were enrolled. Ocular biometry was obtained using A-scan ultrasonography, and reliable images of the optic disc were obtained using a confocal scanning laser ophthalmoscope. The relationship between optic disc area and axial length was assessed using univariate and multivariate models. Results: 281 eyes of 281 subjects were enrolled. Black subjects (n = 157) had significantly larger discs (mean (SD) disc area, 2.12 (0.5) mm 2 ) than white subjects (n = 124; 1.97 (0.6) mm 2 ; t test, p = 0.02). Optic disc area increased with axial length (Pearson's correlation coefficient, r = 0.13, p<0.035) for the entire study population. Multivariate regression models including race, disc area and axial length showed that a significant but weak linear relationship exists between axial length and disc area (partial correlation coefficient 0.14; p<0.024), and with race and disc area (partial correlation coefficient 0.19; p<0.017) when adjusted for the effects of other terms in the model. Conclusion: Increased disc area is associated with longer axial length measurements and African ancestry. This may have implications for pathophysiology and risk assessment of glaucoma.